Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 8 No 1 (2022): NIU Journal of Social Sciences, Vol. 8 No. 1, March 2022, 2024)
This issue of NIU Journal of Social Sciences focuses on Development Administration, Social Philosophy, Educational Management as well as Political Economic Relations. The first part of the Journal addresses issues in Development Administration such as Crime fighting, Economic Repositioning, Nation Building, Service Delivery, Social Development, Resource Control and so on. It is argued in one of the papers that fall in revenue during Covid 19 lockdown has negatively affected the education sector in Nigeria. As the solutions to the challenges educational fundind during COVID-19, the paper recommends among others for the provision of infrastructure for learning, keeping students safe online, improved educational funding and reduction in taxes to educational institutions by government. Section two explores issues in Political Economic Relations such as Multilateral Diplomacy, Religion, Contemporary Security Debacle in West Africa and the Political Economy of Colonial Administration in Africa. In assessing and exploring Nigeria’s multilateral diplomacy, one of the papers in this section uses latent content analysis to mine data from existing documents, journal articles, newspapers, and policy papers to dissect the process of multilateralism in Nigeria’s foreign policy and concluded that Nigeria’s multilateral diplomacy is one of the most complex not only in Africa but also in the global south. In the Section on Educational Management, one of the papers argues that the value of education is underlined by the fact that each society establishes an educational sytstem designed to serve its present and future needs. Education serves as an instrument for stability, change and renewal. Thus, the transmission of knowledge, skills and values is basic and information dissemination has been the key to achieving these laudable goals. Papers in the last section are on Social Psychology. Using Lagos State in Nigeria as a case study, one of the papers in these sections reveals that one of the major challenges confronting mediation and administration of criminal justice in cases of spousal battery are underreporting and under prosecution associated with a myriad of problems accounting for adjournment and withdrawal of cases in court. Following this, the study recommends that society should exhibit zero tolerance to spousal battery. Law enforcement agencies like the Nigeria Police Force (NPF), the Court, non-governmental organizations (NGOs) and the media should champion the promotion of public sensitization and awareness of the laws prohibiting the crime, encourage victims to speak out, report the crime to appropriate authorities and assist victims to press for legal charges in court. Government should also show more commitment in decongesting the Domestic Violent Court and Citizen’s Mediation Centre of civil cases like spousal battery and the provision of free treatment, as well as counseling and rehabilitation, to victims. In all, this edition of NIU Journal of Social Sciences features many interesting research papers. Some of these papers are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them. Readers are therefore advised to make proper use of the ideas presented by the various authors.